Space charge dynamics in epoxy resin under voltage polarity reversal at various temperatures. Issue 5 (3rd November 2020) - Liu, Peng; Zhang, Hongliang; Zhang, Siyu; Su, Xialin; Xie, Zongliang; Peng, Zongren
Abstract: Epoxy resin has been used to cast the core of the dry‐type high voltage direct current bushings and can accumulate space charge under high electric fields at high temperatures, which is believed to be a potential threat to the safe operation of dry bushings, especially under polarity reversal. In this study, results of a study of the evolution of space charge and electric field distribution in epoxy resin, under polarity reversal at 10 and 20 kV/mm, and at temperatures between 40 and 100°C, are presented. The results show that the space charge dynamics in epoxy resin during the test were different at various temperatures. At temperatures no more than 60°C, space charge accumulation within the samples was not obvious. Instead, a low‐frequency dielectric relaxation process maybe occurs during the polarity reversal, which made the charge peaks on the electrodes after the reversal were slightly smaller than those before the reversal. At temperatures no less than 80°C, considering that the applied electric field has little effect on the barrier reductions of the traps within the samples, the space charge dynamics were mainly governed by a thermally activated process, and the depths of the deepest occupied traps were obtain by analysing the transient processes.